Postless Hip Arthroscopy: A Safer Alternative for Treatment of Femoracetabular Impingement Syndrome - Michael B. Held MD, MBA; Liana J. Tedesco MD; Mario H. Lobao MD; T. Sean Lynch MD (SAGE Publishing, 2021)
Background: Hip arthroscopy for femoroacetabular impingement (FAI) syndrome continues to gain popularity and indications for its use are expanding. Though low complication rates have previously been reported, there are iatrogenic complications specific to the use of the perineal post, such as pudendal nerve injuries, and possible pressure skin necrosis that warrant concern in the healthy young patient. The risk of these complications are increased during simultaneous bilateral hip arthroscopy. Indications: We describe a new technique, which will prevent such problems by using a postless pink pad technique in order to achieve adequate hip distraction. Technique Description: Arthroscopic investigation begins with proper, safe patient positioning in order to gain access to the hip joint with sufficient joint distraction. In the postless technique, a dense foam pad is utilized in lieu of a perineal post. The static friction between the pad, bed, and the patient counters the manual gross traction necessary to distract the hip joint while preventing the patient from sliding down or off of the operating table. The postless technique avoids pressure to the perineum and also allows for greater range of motion during dynamic intraoperative examination and femoroplasty. After hip distraction, standard portal placement allows for access to the central compartment in order to assess intraarticular pathology. Once identified on diagnostic arthroscopy, appropriate techniques are utilized to correct acetabular-sided pincer lesions, labral tears, and femoral-sided cam deformities. Results: When discussing this technique with patients, it is important to highlight that it diminishes the possibility of iatrogenic pressure injury to the pudendal nerve and skin of the perineum. The risk of these injuries typically occurs when the pudenal nerve is compressed against the post during traction and abduction. As such, postless technique prevents any compression and pressure to these regions. Discussion/Conclusion: Hip arthroscopy is a minimally invasive, low morbidity technique for treating a variety of chondral, ligamentous, and bony conditions of the hip. However, studies suggest that pudenal nerve injury is seen in up to 4.3% of patients following hip arthroscopy. Given avoidance of iatrogenic post complications, we describe a postless technique for achieving hip distraction during hip arthroscopy.